Los Estados Financieros del Gobierno Autónomo Descentralizado del Cantón Montalvo provincia de Los Ríos de los periodos 2020 – 2021 - Bonilla García, Jessenia Susana (2022)
The Decentralized Autonomous Government of the city of Montalvo is a public entity belonging to the non-financial sector with administrative and financial autonomy that was established in order to satisfy the basic needs that the residents of the city require, therefore, being a relevant entity, it must stay financially stable for well-being in general. In the report developed, a financial analysis was applied to the financial statements of the Montalvo GAD, specifically to the statements of financial position and income statements for the periods 2020-2021, with the aim of knowing the current economic situation of the GAD, since within of its accounting area has presented inconveniences in the fulfillment of its functions, causing with it, that the preparation of the financial statements is not carried out on time, and in its presentation they reflect numerical variations within its accounts. The objective of the report is to know the current economic situation of the entity, through a financial evaluation using the horizontal and vertical method. The case study focused on the Financial Management, tax and social commitment research subline; the applied methodology is the inductive method, which is known because the investigation starts from a particular premise until reaching a general conclusion, the technique to be implemented will be an interview addressed to the current accountant of the entity through the use of a questionnaire. It is worth mentioning that all information that is reflected in the report was developed based on bibliographic information sources in conjunction with the information provided by the entity itself, these documents are the financial statements of the two past periods, 2020 - 2021.